(3GdYbO GdfajS hfRgI GdLdjSs - (3GdWhdhfj , eMeO Hf YHO GdQMef Hf CHj HcQs
(3ChdgG (B:s
(3CeG HYO, aEf CMb eG fWb Hg GddSGf, hCYQH Yfg GdHjGf hCOH GdSjGSI eG CYGf Ydi YeGQI GdCQV, hcdGgeG jQLYGf Edi GdYOd s
(3BNQgG (B:s
(3ef dGfJ cdeJg hLHJ eMHJg GfJgi cdGe SjOfG Ydj Hf CHj WGdH cQe Gddg hLgg, hQVj Gddg Yfg hYf cd GdUMGHI CLeYjf s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B112 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B43 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdCOHs